New drugs on the horizon for cerebral edema: what's in the clinical development pipeline? - Robert, Stephanie M; Reeves, Benjamin C; Alper, Seth L; Zhang, Jinwei; Kahle, Kristopher T (Expert Opin Investig Drugs, 2020)
INTRODUCTION: Research has advanced our understanding of the molecular and cellular mechanisms of cerebral edema and has propelled the development of novel antiedema therapeutics. Current evidence supports aberrant neuro-glial ion transport as a central mechanism that underlies pathological fluid accumulation after central nervous system injury. AREAS COVERED: Novel agents in clinical development show potential in altering the natural history and treatment of cerebral edema. Using the PubMed and Google Scholar databases, we review recent advances in our understanding of cerebral edema and describe agents under active investigation, their mechanism, and their application in recent and ongoing clinical trials. EXPERT OPINION: Pharmacotherapies that target molecular mechanisms underlying the compensatory post-injury response of ion channels and transporters that lead to pathological alteration of osmotic gradients are the most promising therapeutic strategies. Repurposing of drugs such as glyburide that inhibit the aberrant upregulation of ion channels such as SUR1-TRPM4, and novel agents, such as ZT-1a, which reestablish physiological regulation of ion channels such as NKCC1/KCC, could be useful adjuvants to prevent and even reverse fluid accumulation in the brain parenchyma.
Keywords: Animals; Brain Edema; Drug Development; Drug Repositioning; Drugs, Investigational; Humans; Molecular Targeted Therapy

PEHO syndrome caused by compound heterozygote variants in ZNHIT3 gene. - Õunap, Katrin; Muru, Kai; Õiglane-Shlik, Eve; Ilves, Pilvi; Pajusalu, Sander; Kuus, Imbi; Wojcik, Monica H; Reimand, Tiia (Eur J Med Genet, 2020)
PEHO syndrome is characterized by Progressive Encephalopathy with Edema, Hypsarrhythmia, and Optic atrophy, which was first described in Finnish patients. A homozygous missense substitution p.Ser31Leu in ZNHIT3 was recently identified as the primary cause of PEHO syndrome in Finland. Variants in ZNHIT3 have not been identified in patients with PEHO or PEHO-like syndrome in other populations. It has therefore been suggested that PEHO syndrome caused by ZNHIT3 variants does not occur outside of the Finnish population. We describe the first patient outside Finland who carries compound heterozygous variants in ZNHIT3 gene causing PEHO syndrome. Trio genome sequencing was carried out and the identified variants were confirmed by Sanger sequencing. The patient filled all diagnostic clinical criteria of PEHO syndrome. We identified biallelic missense variants in ZNHIT3 gene: the c.92C > T p.(Ser31Leu) variant (NM_004773.3), which is described previously as causing PEHO syndrome and the second novel variant c.41G > T p.(Cys14Phe). There are only eight heterozygous carriers of c.41G > T variant in the gnomAD database and it is predicted damaging by multiple in silico algorithms. The ZNHIT3-associated PEHO syndrome exists outside of the Finnish population.
Keywords: Brain Edema; Databases, Genetic; Edema; Epileptic Syndromes; Female; Finland; Heterozygote; Humans; Infant, Newborn; Mutation, Missense; Neurodegenerative Diseases; Nuclear Proteins; Optic Atrophy; Phenotype; Spasms, Infantile; Transcription Factors; Whole Exome Sequencing; Whole Genome Sequencing

PEHO Syndrome May Represent Phenotypic Expansion at the Severe End of the Early-Onset Encephalopathies. - Gawlinski, Pawel; Posmyk, Renata; Gambin, Tomasz; Sielicka, Danuta; Chorazy, Monika; Nowakowska, Beata; Jhangiani, Shalini N; Muzny, Donna M; Bekiesinska-Figatowska, Monika; Bal, Jerzy; Boerwinkle, Eric; Gibbs, Richard A; et al. (Pediatr Neurol, 2016)
BACKGROUND: Progressive encephalopathy with edema, hypsarrhythmia and optic atrophy (PEHO) syndrome is a distinct neurodevelopmental disorder. Patients without optic nerve atrophy and brain imaging abnormalities but fulfilling other PEHO criteria are often described as a PEHO-like syndrome. The molecular bases of both clinically defined conditions remain unknown in spite of the widespread application of genome analyses in both clinic and research. METHODS: We enrolled two patients with a prior diagnosis of PEHO and two individuals with PEHO-like syndrome. All four individuals subsequently underwent whole-exome sequencing and comprehensive genomic analysis. RESULTS: We identified disease-causing mutations in known genes associated with neurodevelopmental disorders including GNAO1 and CDKL5 in two of four individuals. One patient with PEHO syndrome and a de novoGNAO1 mutation was found to have an additional de novo mutation in HESX1 that is associated with optic atrophy. CONCLUSIONS: We hypothesize that PEHO and PEHO-like syndrome may represent a severe end of the spectrum of the early-onset encephalopathies and, in some instances, its complex phenotype may result from an aggregated effect of mutations at two loci.
Keywords: Brain Edema; Child; Child, Preschool; Female; GTP-Binding Protein alpha Subunits, Gi-Go; Humans; Infant; Male; Mutation; Neurodegenerative Diseases; Optic Atrophy; Phenotype; Protein Serine-Threonine Kinases; Spasms, Infantile